ANALISIS PROFIL POTENSI PROFESI ENTREPRENEUR DI LINGKUNGAN MAHASISWA STIE SEMARANG - Nikita, Deliade; Sunarto, St. (STIE Semarang, 2024)
This study aims to evaluate the entrepreneurial potential of STIE Semarang students based on their self-assessment. Data was collected from 40 respondents via a Google Form questionnaire and analyzed descriptively using cross- tabulation. The study used a Likert scale to measure responses, with results analyzed using a Frequency Distribution (FD) table to examine the distribution of entrepreneurial potential among students overall and by program. The findings indicate that the entrepreneurial potential of Accounting and Management students is generally high, with variations in the following characteristics: Leadership: Accounting 10%, Management 13.33%, Self-Confidence: Accounting 10%, Management 16.66%, Responsibility: Accounting 70%, Management 20%, Thoroughness: Accounting 50%, Management 33.3%, Business Perseverance: Accounting 30%, Management 23.3%, Risk-Taking: Accounting 40%, Management 36.6%, Creativity: Accounting 40%, Management 23.3%